Screening of Multi-drug resistant Colistin Resistant gram-negative Bacteria in Environmental and Clinical Samples from Central India. (International Journal of Food and Nutritional Sciences, 2022)
Colistin is said to be the last resort antibiotic against multi drug resistant gram-negative bacterial infections both in humans and animals. Emergence of colistin resistant bacteria gram-negative bacilli represent a global public health threat that limits therapeutic options for hospitalized patients. In the present study, we describe the occurrence of colistin resistant bacteria in both hospital and in environmental samples in the part of Central India with special reference to Jabalpur area.Methods: For analysis, 16 samples were collected including urine samples from hospital and soil samples from different environmental conditions. Collected isolates were identified using biochemical characterization and tested against different antibiotic susceptibility to observe multi drug resistance.Results: Total of 2 (12.5%) colistin resistant bacteria were isolated out of 16 samples i.e E.coli and Pseudomonas from environment and clinical samples respectedly. They are resistant to different antibiotics showing multi-drug resistance.Conclusions: Presence of multi- drug resistant colistin resistant gram negative bacteria in Central India was observed. The prevalence of colistin resistance in Central India as per our study is low but not negligible. We have to study more about the resistant bacteria and the reason of emergence in our locality.